Hydrophobic modification of fir wood surface via low ppm ATRP strategy. (16th July 2021) - Zaborniak, I.; Macior, A.; Chmielarz, P.; Smenda, J.; Wolski, K.
Abstract: Wood-polymer hybrid material was prepared using an easily scalable supplemental activator and reducing agent atom transfer radical polymerization (SARA ATRP) concept with low ppm catalyst concentration. Polymers with hydrophobic characteristics – poly ( n -butyl acrylate) (P n BA), poly ( tert -butyl acrylate) (P t BA) and poly (methyl methacrylate) (PMMA) were grafted from the fir wood surface in a controlled manner, proved by linear first-order kinetics of polymerization in solution and low dispersity ( M w / M n  = 1.12) of the polymers formed in the reaction mixture. Moreover, the thickness of the polymer brushes grafted from the wood surface was estimated based on the measurements performed for brush decorated silicon wafers that were placed in the reaction mixture. Scanning electron microscopy (SEM) proved successful coverage of the wood by a covalently attached polymer layer, going from sharp-edged untreated wood surface with clearly visible wood cell wall structural elements, to full coverage rough texture with no visible structural components. Water contact angle (Θ) measurements indicated excellent hydrophobic properties of the prepared biohybrid material (Θ ~138°) without notable changes after 120 s of water droplet exposure. Water and acid solution uptake tests confirmed a significant improvement in resistance for absorption of wood samples after modification with polymers. Graphical abstract: Image 1 Highlights: SARA ATRP as an economic and industrial relevant approach for wood modification. SEM visualization of (meth)acrylates decorated fir wood specimens proved coverage by a polymer layer. Significant improvement of fir wood hydrophobicity by a covalently attached polymer layer.